Laws in ecology: diverse modes of explanation for a holistic science? - Gunton, Richard; Gilbert, Francis (Wiley, 2017)
Ecology’s reputation as a holistic and soft science is partly due to widespread misconceptions of its nature as well as shortcomings in its methodology. We show how the pursuit of empirical laws of ecology can foster the emergence of a more unified and predictive ecology based on complementary modes of explanation. Numerical analyses of population dynamics have a distinguished pedigree, spatial analyses successfully generate predictive laws for macroecology and physical analyses are tyically pursued by the ecosystem approach. The most characteristically ecological laws, however, are found in biotic analyses within the ‘functional trait’ paradigm. Holistic credentials for ecology may thus be restored on two bases: its accommodating complementary modes of analysis and explanation, and its having some laws within the least reductionistic mode consistent with its subject matter. These claims, grounded in the aspectual theory of Herman Dooyeweerd, lead to some suggestions for enhancing the versatility and usefulness of ecology – and other sciences – by balancing different research paradigms under a holistic vision.